Hypothyroidism and oxidative stress: differential effect on the heart of virgin and pregnant rats - Carmona Viglianco, Yamila Virginia (2014)
The present study investigates the effects of hypothyroidism on both the redox state and the thyroid hormone receptors expression in the heart ventricle of virgin and pregnant rats. Hypothyroid state was induced by 6-n-propyl-2-thiouracil in drinking water given to Wistar rats starting 8 days before mating until day 21 of pregnancy or for 30 days in virgin rats. Serum paraoxonase-1 (PON-1) activity, serum and heart nitrites, and thiobarbituric acid-reactive substances (TBARS) were analyzed. Heart protein oxidation, as carbonyls, and copper-zinc superoxide dismutase (CuZnSOD), glutathione peroxidase (GPx), and catalase (CAT) activities, were determined. In addition, heart expressions of NADPH oxidase (NOX-2), CAT, SOD, GPx, and thyroid receptors (TRα and TRβ) mRNA were assessed by RT-PCR. Inducible and endothelial Nitric Oxide Synthase (iNOS and eNOS) were determined by Western blot. Hypothyroidism in the heart of virgin rats decreased TRα and TRβ expressions, and induced oxidative stress, leading to a decrease of nitrites and an increase of carbonyls, NOX-2 mRNA, and GPx activity. A decreased PON-1 activity suggested low protection against oxidative stress in blood circulation. Pregnancy reduced TRα and TRβ mRNA expressions and induced oxidative stress by increasing nitrite and TBARS levels, SOD and CAT activities and NOX-2, eNOS and iNOS expressions, while hypothyroidism, emphasized the decreases of TRα mRNA levels and did not alter the redox state in the heart. TR expressions and redox balance of rat hearts depend on the physiological state. Pregnancy per se seems to protect the heart against oxidative stress induced by hypothyroidism.